Role of spin-transfer torques on synchronization and resonance phenomena in stochastic magnetic oscillators - Accioly, Artur; Locatelli, Nicolas; Mizrahi, Alice; Querlioz, Damien; Pereira, Luis G.; Grollier, Julie; Kim, Joo-Von (Journal of applied physics, 2016)
A theoretical study on how synchronization and resonance-like phenomena in superparamagnetic tunnel junctions can be driven by spin-transfer torques is presented. We examine the magnetization of a superparamagnetic free layer that reverses randomly between two well-defined orientations due to thermal fluctuations, acting as a stochastic oscillator. When subject to an external ac forcing, this system can present stochastic resonance and noise-enhanced synchronization. We focus on the roles of the mutually perpendicular damping-like and field-like torques, showing that the response of the system is very different at low and high frequencies. We also demonstrate that the field-like torque can increase the efficiency of the current-driven forcing, especially at sub-threshold electric currents. These results can be useful for possible low-power, more energy efficient applications.